The Implementation of the Complete Systematic Land Registration (PTSL) Program in Malang Regency Land Office - Budiman, Arif (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Pendaftaran Tanah Sistematis Lengkap (PTSL) or Complete Systematic Land Registration is a program under the Ministry of Agrarian Affairs and Spatial Planning/ National Land Agency (ATR/ BPN) in response to new directives from President Joko Widodo in 2016 to register all yet 79 million unregistered land parcels before 2025. The organization and its officers are still adapting to the sudden change in work rhythm from the usual target of 1 million land parcels per year to 5 million land parcels that gradually increases every year further. This research employs the descriptive method with the qualitative approach to study the process of PTSL program implementation in Malang Regency Land Office during the year of 2017 and 2018. By measuring success of the PTSL program implementation, it can be concluded that the goal of PTSL program in Malang Regency Land Office was achieved and PTSL program was delivered as expected.